An inverse coefficient problem for a parabolic equation in the case of nonlocal boundary and overdetermination conditions - Ismailov, Mansur I.; Kanca, Fatma (Wiley, 2011)
In this paper, the inverse problem of finding the time-dependent coefficient of heat capacity together with the solution of heat equation with nonlocal boundary and overdetermination conditions is considered. The existence, uniqueness and continuous dependence upon the data are studied. Some considerations on the numerical solution for this inverse problem are presented with the examples. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: parabolic equation; inverse problem; nonorthogonal systems of functions; nonlocal boundary conditions; integral overdetermination condition